2023
DOI: 10.3389/fendo.2023.1184747
|View full text |Cite
|
Sign up to set email alerts
|

Urinary iodine concentration and its associations with thyroid function in pregnant women of Shanghai

Abstract: ObjectiveTo assess the iodine status and its associations with thyroid function in pregnant women of Shanghai.MethodsIn this cross-sectional study, a total of 562 pregnant women were enrolled from January to December 2021. Both serum thyroid-stimulating hormone (TSH), free triiodothyronine (FT3), free thyroxine (FT4), thyroid peroxidase antibody (TPOAB), thyroglobulin antibody (TGAB), and urinary iodine concentration (UIC) were detected. Participants were divided into four groups based on their UIC values. Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Our study found that UIC had no correlation with thyroid function indicators or thyroid diseases. However, a recent study showed that the relationship between the prevalence of UIC and thyroid diseases embodied a U-shaped curve [ 27 ]. This may be due to the fact that there are many influencing factors on UIC in pregnant women, and individual UIC levels fluctuate greatly, so they cannot accurately reflect the actual iodine nutritional status of individual pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that UIC had no correlation with thyroid function indicators or thyroid diseases. However, a recent study showed that the relationship between the prevalence of UIC and thyroid diseases embodied a U-shaped curve [ 27 ]. This may be due to the fact that there are many influencing factors on UIC in pregnant women, and individual UIC levels fluctuate greatly, so they cannot accurately reflect the actual iodine nutritional status of individual pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Both insufficient ( 112 ) and excessive ( 117 ) iodine intake may lead to maternal hypothyroidism. Researchers have explored the relationship between iodine intake and maternal thyroid hormone levels, with adequate iodine intake considered helpful in maintaining normal thyroid function ( 118 , 119 ) Multiple studies focus on monitoring postpartum mothers’ iodine nutrition status ( 120 122 ), aiding in the formulation of iodine supplementation strategies and providing guidance on iodine intake recommendations. Overall, researchers have conducted in-depth investigations into the relationship between iodine and Maternal Hypothyroidism to promote effective management of the health of pregnant and postpartum women.…”
Section: Discussionmentioning
confidence: 99%
“…The results of other studies have shown a similar trend. For example, one study conducted in Shanghai (China) displayed that both low and high urine iodine concentration was related to thyroid function and autoimmunity, it is important to keep an optimal iodine nutrition status during gestation (5). It is worth noting that the impact of iodine nutritional status on the occurrence of thyroid diseases is widely recognized, as inadequate iodine intake hampers the maintenance of normal physiological morphology and function of the thyroid gland.…”
Section: Discussionmentioning
confidence: 99%
“…However, nowadays many studies only focused on the iodine nutritional status of pregnant women, and seldom studies concerned on the effect of iodine nutrition on the thyroid function of pregnant women and their neonatal outcome. Among these studies, one conducted in Shanghai (China) displayed that both low and high urine iodine concentration was related to thyroid function and autoimmunity (5). A cross-sectional study in the southeast coast of China showed that serum iodine concentration (SIC) negatively correlated with thyroid stimulating hormone (TSH), and positively correlated with other thyroid function indicators, which indicating SIC may serve as a composite indicator of iodine nutritional status (6).…”
Section: Introductionmentioning
confidence: 99%